An approach to vmat on radiation therapy treatments of pelvic and paraaortic lymph nodes. (September 2016) - del Castillo, A.; Miguel, D.; Perez-Garcia, H.; Benito, M.; Sanchez-Belda, M.; Alonso, D.; de Frutos, J.; Andrés, C.; Agulla, M.; Pérez, C.; Gomez, M.; Torres, R.; et al.
Abstract: Introduction: When large volumes need to be irradiated multiple organs at risk are involved. There is no doubt about the preeminence for conformal index and sparing of critical structures for VMAT, but an alternative regarding the use of single or multiple isocenter shows a subject for detailed analysis. Purpose: To compare VMAT in treatment of pelvic and paraaortic lymph nodes using single or double isocenter. Materials and Methods: A set of five patients are selected. For every patient an expert radiation oncologist contoured on CT images volumes and organs according to the RTOG guidelines. Plans were done in Eclipse 11 using Accuros XB algorithm for 6MV X-rays from a Clinac 2100-120MLC, using VMAT double full rotation arc with collimator rotation 30°-330°. For isocenter placement the Arc Geometric tool are used, for double isocenter only we allowed only longitudinal couch movement between isocenters. The same plan objectives are used for every single isocentre plan, but for organs at risk adjustments are made during optimization in order to get the best result for each case. When using double isocentre the VMAT paraoortic plan is used as dose base for VMAT pelvic optimization. Results: Single isocenter shows higher irradiated volumes V5 are 1–2% and V20 up to 14%, sparing for liver and kidneys are improve for the double isocenter but with an average increase of 10% in monitor units each plan. Conclusion: Double isocenter plan improves organ sparing but worse PTV dose homogeneity. Disclosure: No conflicts of interest to declare.